Employee Delight in the Future of Work - Prasoon, Pranav (Digital Repository of Theses, 2024)
Pandemic changed the entire corporate ecosystem; the workplace, workforce and work were rethought once again in the new normal. While digital workplace and hybrid workforce are common words in all the organizations these days the critical issues for organizations today are to uplift the morale of the employees and bring fortitude in the workplace. The uncertainty and anxiety have given rise to ‘cognitive-dissonance’ which is contagious from one industry to another and has given rise to massive attrition – almost double than it used to be earlier. Reports suggest that more than 1/3rd of the workforce is completely disengaged and searching for jobs – because of constant fear, digital shift, lack of collaboration which has resulted in these sudden resignations. The COVID-19 pandemic has had a significant impact on the corporate ecosystem. How we work, the places we work, and how we interact with colleagues have all changed. The pandemic has accelerated the shift towards remote work and forced businesses to rethink their employee motivation and retention strategies. My research using survey, interviews and assimilation of various documents and studies has revealed that the impact of the pandemic on work processes, the shift to remote work, and the strategies organisations use to motivate and retain employees are both legacy & innovative. The research suggests that businesses that adopt a flexible and adaptable approach can continue to thrive in the new normal. My study so far has revealed that the impact of COVID-19 pandemic has changed the way we worked majorly in terms of work processes, there is a major shift to remote working which has changed the work-psychology of an employees and every employer is experimenting in various ways to motivate and retain employees. As a result, many organisations had to implement new work strategies to cope with the unprecedented situation. Reopening of workplace and bring the employees back to business with a high morale and certain level of motivation is a herculean task for entire HR fraternity across domains. The workings on ‘Customer delight’ has taken a backseat and it is pristine and is of high priority to explore the topic of ‘Employee Delight in the future of work’.